(untitled) (Research, Society and Development, 2023)
Juvenile idiopathic arthritis (JIA) is a form of chronic arthritis that begins before age 16. Environmental, socioeconomic and therapeutic factors can influence adherence to treatment, severity and perception of the disease. The objective was to identify adherence rates and factors that hinder treatment in patients with JIA in Brazil and worldwide. This is a literature review, conducted from 1999 to 2020, based on the search for publications in the following databases: PubMed, LILACS, Scielo and Science direct. After applying the inclusion and exclusion criteria, 11 of the 189 publications remained. Of the 11 selected studies on adherence, 4 were in the United States, 3 in Canada, 1 in Spain and 4 in Brazil. With regard to adherence, the United States had a maximum value of 82%. Brazil, on the other hand, presented a maximum value of 76%. The selected studies also revealed that the main barrier to adherence in patients with JIA is fear of the consequences of using the therapy. In Brazil, other factors, such as: high cost, difficult access to health services, specialists and medication, as well as geographic distance, interfere with adherence. Brazil presents treatment adherence values similar to those found in developed countries, however, there are still local and regional disparities regarding adherence. These disparities can be explained in part by the difficulty in accessing both health services and medication and the abandonment of pharmacotherapeutic follow-up.